HEPATOPROTECTIVE EFFECT OF PERILLYL ALCOHOL (POH) ON HIGH-FAT DIET-LOW-DOSE STREPTOZOTOCIN-INDUCED TYPE 2 DIABETES IN EXPERIMENTAL RATS - TOWSEEF HASSAN; ELANCHEZHIYAN C; INSHA NASEER (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the present study was to investigate the hepatoprotectivity effect of perillyl alcohol in high-fat diet (HFD)-low-dose streptozotocin (STZ)-induced diabetic rats. Methods: Diabetes was induced in male albino Wistar rats by 4 weeks diet manipulation followed by a low single intraperitoneal injection of STZ (35 mg/kg body weight). Perillyl alcohol was administered orally (50 mg/kg body weight and 100 mg/kg body weight) for 30 days. Glibenclamide was used as a standard drug and given orally 6 mg/kg body weight. At the end of treatment period, levels of alkaline phosphatase (ALP), aspartate transaminase (AST) alanine transaminase (ALT), and bilirubin and serum protein were measured in serum of experimental rats. Histopathological studies of liver were also done with microscope. Results: The levels of ALP, AST ALT, and bilirubin were increased significantly in HFD-STZ-induced diabetic rats. Perillyl alcohol-treated diabetic rats showed marked restoration in the activity of ALP, AST, ALT, and bilirubin when compared with diabetic control rats. Perillyl alcohol and glibenclamide drug-treated rats showed reversible tissue regeneration with prominent hepatocytes. Conclusion: The present results clearly indicate that the perillyl alcohol has a potent efficacy for hepatoprotective effect in HFD- low-dose STZ-induced diabetic rats.